Nettle (Urtica Dioica L.) Modulates Angiogenesis by Targeting the PI3K/AKT/eNOS Pathway in Prostate Cancer - Abduladheem AL-Attabi; Mohammed Sabah Mohammed; Noor Ali Yazi AL-Khazali; Sami Awad Alkubaisy; Muna S. Merza; Mohanad Ali Abdulhadi; Yasser Fakri Mustafa (Middle East Journal of Cancer, 2025)
Background: Medicinal plants, predominantly those rich in polyphenolic mixtures, have been recommended to have chemopreventive and chemotherapeutic effects. This study aimed to investigate the effects of Urtica dioica L. extract (UDE) on angiogenesis and prostate cancer (PCa) cell progression through the phosphoinositide 3-kinase/Protein kinase B/ endothelial nitric oxide synthase (PI3K/AKT/eNOS) signaling pathway.Method: This study employed an in vitro experimental design using PCa cell lines. To gain mechanistic insights into the anti-proliferative properties of UDE, PCa cell proliferation was assessed using an MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide) assay in DU-145 cells (incubated for 48h). Also, we explored expression patterns of PI3K/AKT/eNOS pathway genes with therapeutic potential (with 50 µg/ml of UDE) in DU-145 cells by quantitative polymerase chain reaction and western blotting assay. Furthermore, we applied the ELISA cell death assay kit to reveal the apoptotic effects of UDE on PCa cells. Statistical analysis was determined using the Mann-Whitney U test and P ≤ 0.05 was considered statistically significant. Results: UDE significantly decreased the cell viability after 48 h of treatment in DU-145 cells. Also, reducing the vascular endothelial growth factor (VEGF) levels revealed anti-angiogenic outcomes. Also, the eNOS level in the PI3K/AKT/eNOS pathway is dramatically alleviated upon treatment with UDE. Moreover, the apoptosis rate of DU-145 cells was enhanced compared with the control group.Conclusion: The antitumoral activity of UDE was prominent in its persuasive anti-angiogenic potential, as UDE contributed to a striking diminish in PI3K/AKT/eNOS pathway in PCa and diminished the VEGF expression.